Interações sociais em rede de produção científica acadêmica sob a perspectiva da teoria ator-rede : caso do Programa de Pós-graduação em Tecnologia e Sociedade (PPGTE/UTFPR) - Destefani, Rodrigo Deren (2016)
This research aims to describe social interactions that occur in a scientific production network, from the perspective of Actor-Network Theory in a Graduate Interdisciplinary Program, the Graduate Program in Technology and Society – PPGTE of the Federal Technological University of Paraná - UTFPR. In terms of methodology, the research is qualitative and descriptive nature in relation to their goals. It makes use of the technical procedures of bibliographic research, documentary research, content analysis and survey, through semi-structured interviews. On the main results, it was possible to categorize the actors in the network, demonstrating that Professor-Researcher-Advisor, especially the older and with greater range of action, act as mediators in the network and the student-mentees as intermediaries. It was also possible to identify some of the most relevant actors for the emergence of the PPGTE network and its maintenance, stabilization and strengthening. The theme of interdisciplinarity emerges in the research as important singularity that provides registering controversy in the network, in the process of training and maintenance. Still, the development agencies as actants in the network were found, also operating as prescriptive spaces where it is possible to identify policies to encourage interdisciplinarity, inducing PPGs networks like PPGTE. For the actuation of the human actors, micro-networks, formed in lines and research groups also showed how important actants in the academic scientific production process. It was also demonstrated the important role of institutional management as intermediary in PPGTE deployment process.